Emergency guiding and monitoring applications in indoor 3D environments by wireless sensor networks. (7th September 2006) - Pan, Meng-Shiuan; Tsai, Chia-Hung; Tseng, Yu-Chee
Recently, Wireless Sensor Networks (WSNs) have been widely discussed in many applications. In this paper, we propose a novel Three-Dimensional (3D) emergency service that aims to guide people to safe places when emergencies happen. At normal time, the network is responsible for monitoring the environment. When emergency events are detected, the network can adaptively modify its topology to ensure transportation reliability, quickly identify hazardous regions that should be avoided and find safe navigation paths that can lead people to exits. In particular, the structures of Three-Dimensional buildings are taken into account in our design. Simulation results shows that our protocols can adapt emergencies quickly at low message cost and can find safer paths to exits than existing results